Dampak Keberadaan Tambang Pasir Terhadap Kondisi Sosial Ekonomi Masyarakat di Desa Cimpu Utara Kecamatan Suli Kabupaten Luwu - Nyompa, Sukri; Sari Dewi, Nur Adha; Sideng, Uca (LaGeografia, 2020)
This study aims to determine: 1) The socio-economic condition of sand miners 2.) The level of income of sand miners before and after the existence of a sand mine in Cimpu Utara Village, Suli District, Luwu Regency. This research method uses descriptive qualitative. The population in this study is the owner and labor of sand miners totaling 36 people. Data collection was carried out using observation techniques, interviews, and documentation. Data were analyzed descriptively qualitatively. The results of this study indicate that: 1) The socio-economic conditions of the people who work as sand mines are aged 40-44 years as much as 30.55%,. graduated from junior high as much as 36.11%. The previous respondents' livelihoods were entrepreneurs, farmers and fishermen. 2) The impact of the existence of a sand mine on the socio-economic conditions of the community that is researchers conclude the impact after the existence of a sand mine is very influential on the level of community income. It can be seen from the income before the sand mine Rp. 375.000-583.000/month while the income after the sand mining is around Rp. 512,000 - 6,250,000 / month.